2013
DOI: 10.1002/cbdv.201200406
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Apoptosis‐Inducing Activities of Steviol and Isosteviol Derivatives against Human Cancer Cell Lines

Abstract: Seventeen steviol derivatives, i.e., 2-18, and 19 isosteviol derivatives, i.e., 19-37, were prepared from a diterpenoid glycoside, stevioside (1). Upon evaluation of the cytotoxic activities of these compounds against leukemia (HL60), lung (A549), stomach (AZ521), and breast (SK-BR-3) cancer cell lines, nine steviol derivatives, i.e., 5-9 and 11-14, and five isosteviol derivatives, i.e., 28-32, exhibited activities with single-digit micromolar IC(50) values against one or more cell lines. All of these active c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 28 publications
1
34
0
1
Order By: Relevance
“…Recent studies have revealed several potential mechanisms of action of isosteviol derivatives for anticancer activity [11,27]. From our gene microarray data from breast cancer patient tissues, MMP11 was found to be upregulated while HPSE2 was downregulated in breast cancer compared with normal control [28,29].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Recent studies have revealed several potential mechanisms of action of isosteviol derivatives for anticancer activity [11,27]. From our gene microarray data from breast cancer patient tissues, MMP11 was found to be upregulated while HPSE2 was downregulated in breast cancer compared with normal control [28,29].…”
Section: Resultsmentioning
confidence: 88%
“…In particular, since the end of the 1990s, ent-beyrane diterpenoid isosteviol has attracted a great deal of attention from medicinal chemists as a native scaffold for organic chemistry and drug discovery [1][2][3]. With its unique rigid skeletal structure with six stereo centers, isosteviol derivatives have been shown to have numerous biological activities [4][5][6][7][8][9], particularly in the anticancer area [10][11][12][13][14][15].…”
mentioning
confidence: 99%
“…SW480 cells were incubated with the test compound (0, 0.25, 0.50 and 1.00 mg/l, respectively) for 24 h, and then the cells were analyzed by means of flow cytometry (Fig. [23] [24] In normal cells, PS is predominantly present on cytosolic side of the membrane, while it gets translocated towards outer side of the membrane when cells undergo apoptosis. Apoptotic cells can be detected by virtue of binding of annexin V-FITC to phosphotidyl serine (PS) present on the outer side of the cell membrane.…”
Section: Apoptosis-inducing Activity Of Compound 17mentioning
confidence: 99%
“…또한, 스테비올과 그 유도체인 스테비 오사이드, 리바우디오사이드는 인체 유해성에 대해 보 고되지 않았고 피부 섬유아세포 콜라젠 합성을 통해 피부 탄력 향상 및 주름 개선 효과가 보고되어 있다 [3]. 특히 스테비올에 여러 개의 당이 결합된 스테비오사이 드는 고농도 조건에서도 별다른 독성이 나타나지 않는 것으로 알려져 안전성이 입증되었고 인간 암세포에 대 해 세포사멸(apoptosis)을 유발한다고 알려져 있다 [4,5].…”
Section: 서 론unclassified